Analisis Kebutuhan Pendidikan dan Pelatihan Kepala Madrasah Tsanawiyah di Lampung Timur - Septiani Selly Susanti; Anita Oktaviana; Kurniasih, Apri; Dhoni Kurniawati (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2023)
This research was conducted to: analyze the performance predicate of Madrasah principals, analyze the average performance predicate of Madrasah principals and analyze the education and training needs of Madrasah Tsanawiyah principals in East Lampung. The research was conducted at 9 Madrasah Tsanawiyah in East Lampung. The research method used is descriptive quantitative. Data collection techniques were: interviews, documentation and observations which consisted of 4 main performance indicators of madrasah principals, namely: Madrasah development efforts, implementation of managerial tasks, entrepreneurial development, and supervision of teachers and Madrasah education staff. The results showed that: 1) there were 2 Headmaster of MTs who received the predicate of Very Good performance, 2 Headmasters of MTs received the predicate of Good performance, 3 headmasters of MTs received the predicate of Fair performance, and 2 Headmasters of MTs received the predicate of Moderate performance. 2) The average value of the performance of Madrasah Tsanawiyah headmasters in East Lampung on Madrasah development indicator is 77.43 (Good), implementation of managerial tasks is 79.75 (Good), entrepreneurship development is 68.66 (Enough), and Supervision of teachers and education staff is 62.87 (Enough) . 3) The educational and training needs of Madrasah Tsanawiyah headmasrters in East Lampung are in the components of entrepreneurship development and supervision of teachers and education staff.